Drug Reaction with Eosinophilia and Systemic Symptoms Syndrome in a Child with Cystic Fibrosis - Ahmed Abushahin; Haneen Toma; Sara G. Hamad; Mutasim Abu-Hasan (Case Reports in Immunology)
Background. Drug reaction with eosinophilia and systemic symptoms (DRESSs) syndrome is an idiosyncratic drug-induced reaction that rarely occurs in children but can lead to serious complications. It manifests most commonly with fever, extensive skin eruptions, and eosinophilia. Symptoms typically develop two to six weeks after the initiation of the inciting drug. Visceral organ involvement especially the liver can also occur and if not recognized early and the inciting drug is not stopped immediately, it can lead to liver failure. Therefore, early diagnosis is important but can be very challenging because of disease rarity, lack of a diagnostic test, and its overlap with other common pediatric allergic and infectious conditions. Case Presentation. A 2.5-year-old boy with known diagnosis of cystic fibrosis, bilateral bronchiectasis, pancreatic insufficiency, and chronic airway colonization with Pseudomonas aeruginosa was admitted to our hospital with acute pulmonary exacerbation of CF lung disease. He was treated with intravenous piperacillin-tazobactam and intravenous amikacin in addition to airway clearance. On day 18 of treatment, the patient developed high grade fever followed by diffuse erythematous and pruritic maculopapular rash. Blood tests showed high eosinophilia, high C-reactive protein (CRP), and high liver enzymes levels. The clinical features and the laboratory findings were consistent with the DRESS syndrome. Therefore, all antibiotics were discontinued. Progressive resolution of the symptoms was observed within two days. Laboratory abnormalities were also normalized in the follow-up clinic visit 4 months later. Conclusion. Our case demonstrates the importance of early recognition of the DRESS syndrome in children who develop fever and skin rashes with eosinophilia while undergoing long-term antibiotic treatment. Prompt discontinuation of the offending drug is the cornerstone therapy and results in the resolution of symptoms and prevention of serious complications.